Epilepsy surgery in children with accompanying impairments - Olsson, Ingrid; Danielsson, Susanna; Hedström, Anders; Nordborg, Claes; Viggedal, Gerd; Uvebrant, Paul; Rydenhag, Bertil (European journal of paediatric neurology, 2013)
The aim of this study was to assess seizure outcome 2 years after epilepsy surgery in a consecutive series of paediatric patients, with special focus on children with learning disabilities and other neuroimpairments in addition to the epilepsy. Outcome 2 years after surgery was assessed in 110 of 125 children operated upon for drug resistant epilepsy in Gothenburg 1987–2006. More than half of the children had learning disabilities, 43% motor impairments and 30% a neuropsychiatric diagnosis. Fifty-six per cent of those with an IQ < 70 became seizure-free or had a >75% reduction in seizure frequency, and two thirds if the operation was a resection. The corresponding figure in those with more than 100 seizures per month was 15 out of 31, and another seven had a 50–75% reduction in seizure frequency. The message is that learning disability, motor impairment and psychiatric morbidity should not be contraindications for paediatric epilepsy surgery. More than half of the children with learning disabilities had a worthwhile seizure outcome, with even better results after resective surgery. Children with drug resistant epilepsy and additional severe neurological impairments should have the benefit of referral to a tertiary centre for evaluation for epilepsy surgery.